Plant growth-promoting rhizobacteria associated with avocado display antagonistic activity against Phytophthora cinnamomi through volatile emissions - Méndez-Bravo, Alfonso; Cortazar-Murillo, Elvis Marian; Guevara-Avendaño, Edgar; Ceballos-Luna, Oscar; Rodríguez-Haas, Benjamín; Kiel-Martínez, Ana L.; Hernández-Cristóbal, Orlando; Guerrero-Analco, José A.; Reverchon, Frédérique (PLOS ONE, 2018)
Rhizobacteria associated with crops constitute an important source of potentially beneficial microorganisms with plant growth promoting activity or antagonistic effects against phytopathogens. In this study, we evaluated the plant growth promoting activity of 11 bacterial isolates that were obtained from the rhizosphere of healthy avocado trees and from that of avocado trees having survived root rot infestations. Seven bacterial isolates, belonging to the genera Bacillus, Pseudomonas and Arthrobacter, promoted in vitro growth of Arabidopsis thaliana. These isolates were then tested for antagonistic activity against Phytophthora cinnamomi, in direct dual culture assays. Two of those rhizobacterial isolates, obtained from symptomatic-declining trees, displayed antagonistic activity. Isolate A8a, which is closely related to Bacillus acidiceler, was also able to inhibit P. cinnamomi growth in vitro by 76% through the production of volatile compounds. Solid phase microextraction (SPME) and analysis by gas chromatography coupled with mass spectrometry (GC-MS) allowed to tentatively identify the main volatiles emitted by isolate A8a as 2,3,5-trimethylpyrazine, 6,10-dimethyl-5,9-undecadien-2-one and 3-amino-1,3-oxazolidin-2-one. These volatile compounds have been reported to show antifungal activity when produced by other bacterial isolates. These results confirm the significance of rhizobacteria and suggest that these bacteria could be used for biocontrol of soil borne oomycetes through their volatiles emissions.